"Science and Spiritual Quest: Proceedings of the 4th All India Students Conference on Science and Spiritual Quest 27-29 Dec 2008, NIT Trichi" - Mishra (Subhash C); Chidambaram (M); Ghosh (Sudipto) Ed. (Tiruchirapalli, 2008)
Science - Proceedings
Keywords: Science - Proceedings